A significant decrease in diagnosis of primary progressive multiple sclerosis: A cohort study. (July 2016) - Westerlind, Helga; Stawiarz, Leszek; Fink, Katharina; Hillert, Jan; Manouchehrinia, Ali
Background: Several reports indicate changes to prevalence, incidence, female-to-male ratio in multiple sclerosis. Diagnostic criteria, course definitions and clinical management of the disease have also undergone change during the recent decades. Objective: To investigate temporal trends in the diagnosis of primary progressive multiple sclerosis (PPMS) in Sweden. Methods: Through the Swedish MS registry we investigated the proportion of PPMS diagnosis in birth, diagnosis and age period cohorts using Poisson regression. Results: A total of 16, 915 patients were categorised into six birth-cohorts from 1946 to 1975 and seven date-of-diagnosis-cohorts from 1980 to 2014. We observed a decrease in the uncorrected analysis of diagnosis of PPMS from 19.2% to 2.2% and an average decrease of 23% ( p < 0.001) per 5-year birth-cohort in the adjusted analysis. An average 21% ( p < 0.001) decrease per diagnosis-cohort was seen. In the age-specific diagnosis period cohorts the same decreasing trend of PPMS diagnosis was observed in almost all groups. Conclusion: The diagnosis of PPMS has significantly decreased in Sweden specifically after introduction of disease-modifying treatments. Such decrease can have severe impacts on the future research on PPMS. Our data also suggest that the current trend to emphasise presence or absence of inflammatory activity is already reflected in clinical practice.